A serum protein adsorption profile on BCP ceramics and influence of the elevated adsorption of adhesive proteins on the behaviour of MSCs. Issue 45 (1st November 2018) - Wang, Jing; Chen, Xuening; Guo, Bo; Yang, Xiao; Zhou, Yong; Zhu, Xiangdong; Zhang, Kai; Fan, Yujiang; Tu, Chongqi; Zhang, Xingdong
Abstract : Schematic description of the experimental design and results. Abstract : Protein adsorption plays a key role in bone repair and regeneration by affecting cell behavior. In this study, a biphasic calcium phosphate (BCP) ceramic, with excellent osteoinductivity, was chosen to investigate its serum protein adsorption profile using isobaric tags for relative and absolute quantification (iTRAQ) proteomics technology. 281 differentially adsorbed serum proteins and the involved biological processes were confirmed by the combination of Gene Ontology (GO) annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. The differentially adsorbed adhesive proteins in the extracellular matrix (ECM)–receptor interaction pathway were further selected to investigate their roles in the behavior of mesenchymal stem cells (MSCs). Pre-coating and blockage experiments revealed that both adsorbed vitronectin (VN) and laminin (LN) could promote the attachment, proliferation and osteogenic differentiation of MSCs on the BCP ceramic by interacting with different integrin subunits. It is revealed that the up-regulated expressions of integrin α2, αv and β3, β5 could contribute to VN-mediated MSC functions, and the elevated gene expressions of α6 and β1, β4 could be related to the LN-participated process. The above results proved that the preferential protein adsorption on a biomaterial should be vital for modulating MSC functions in the course of material-mediated osteoinductivity.